2010
DOI: 10.1017/s0022109010000682
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Institutional Ownership

Abstract: In this study we examine the relation between corporate governance and institutional ownership. Our empirical results show that the fraction of a company’s shares that are held by institutional investors increases with the quality of its governance structure. In a similar vein, we show that the proportion of institutions that hold a firm’s shares increases with its governance quality. Our results are robust to different estimation methods and alternative model specifications. These results are consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
304
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 487 publications
(334 citation statements)
references
References 62 publications
23
304
2
5
Order By: Relevance
“…'Managerial signalling theory' mengatakan bahwa direktur memiliki lebih banyak informasi mengenai perusahaan daripada pemegang saham outsiders (Bebchuk dan Weisbach, 2010). Oleh karena itu, direktur lebih mungkin mengeksploitasi informasi orang dalam terhadap ketidakberuntungan pemegang saham outsiders (Demsetz dan Lahn, 1985), yang mana dapat mempunyai pengaruh negatif terhadap kinerja keuangan dan nilai perusahaan (Chung dan Zhang, 2011;Ntim, et al, 2012). Berdasarkan uraian diatas dapat dihipotesis sebagai berikut: H2: Kepemilikan saham oleh direktur berpengaruh positif (negatif) terhadap kinerja keuangan bank-bank yang terdaftar di Bursa Efek Indonesia tahun 2011-2014.…”
Section: Kajian Teoriunclassified
“…'Managerial signalling theory' mengatakan bahwa direktur memiliki lebih banyak informasi mengenai perusahaan daripada pemegang saham outsiders (Bebchuk dan Weisbach, 2010). Oleh karena itu, direktur lebih mungkin mengeksploitasi informasi orang dalam terhadap ketidakberuntungan pemegang saham outsiders (Demsetz dan Lahn, 1985), yang mana dapat mempunyai pengaruh negatif terhadap kinerja keuangan dan nilai perusahaan (Chung dan Zhang, 2011;Ntim, et al, 2012). Berdasarkan uraian diatas dapat dihipotesis sebagai berikut: H2: Kepemilikan saham oleh direktur berpengaruh positif (negatif) terhadap kinerja keuangan bank-bank yang terdaftar di Bursa Efek Indonesia tahun 2011-2014.…”
Section: Kajian Teoriunclassified
“…As a consequence, Chung and Zhang (2011) point that the level of corporate governance increases with the rise of financial institutions ownership, suggesting that good governance allow financial controlling shareholders to exert an active monitoring role over firms in order to ensure the return for their investment.…”
Section: Financial Institutions Ownershipmentioning
confidence: 99%
“…They examined institutional investors' portfolio holdings, and found that their investment decisions appear to be related to their revealed preferences. Chung and Zhang (2011) showed that the fraction of a company's shares held by institutional investors increase with the quality of its governance structure and the proportion of institutions holding a firm's shares increase with its governance quality. These results are consistent with the conjecture that institutional investors gravitate to stocks of companies with good governance structure to meet fiduciary responsibility as well as to minimise monitoring and exit costs.…”
Section: Ownership Identitymentioning
confidence: 99%